Dual-mode security anticounterfeiting and encoding by electrospinning of highly photoluminescent spiropyran nanofibers. Issue 30 (8th July 2021) - Azimi, Reza; Abdollahi, Amin; Roghani-Mamaqani, Hossein; Salami-Kalajahi, Mehdi
Abstract : Electrospinning of photochromic/fluorescent spiropyran copolymer solutions for security marking of cellulosic documents to induce dual-security anticounterfeiting characteristics. Abstract : The application of photochromic materials in the development of anticounterfeiting technologies has shown a significant growth in recent years because of their advantages in displaying dual-mode security as simultaneous photochromic coloration and fluorescence emission. Photochromic copolymers based on styrene and spiropyran (5, 10, and 20 wt% with respect to styrene) with carboxylic acid chain end groups were synthesized by solution polymerization. The chemical structure, thermal behavior, and optical characteristics of the copolymers were studied using proton nuclear magnetic resonance spectroscopy, differential scanning calorimetry, and UV-vis spectroscopy. The copolymer solutions in toluene and DMF were electrospun to yield photochromic nanofibers. The electrospun nanofibers from the copolymer solutions in toluene showed a well-defined morphology, a smooth surface, and a narrow size distribution in their diameter. These nanofibers were applied on cellulosic papers and banknotes for the induction of dual-mode security with a fast and facile authentication strategy. The induced security marks are virtually invisible under visible light and become visible by photochromic coloration from colorless to purple after UV irradiation. They also displayed red fluorescence emission under UV irradiation. Both the photochromic coloration and fluorescence emission showed high intensities, the security marks were rapidly authenticated upon UV irradiation, and this process was fully reversible for several cycles of UV/visible light irradiation because of the higher photofatigue resistance of the spiropyran-containing copolymers. These advantages originated from the high surface area of the photochromic nanofibers leading to higher light absorption and subsequent intense optical responses as coloration and fluorescence emission. Finally, a fast and facile anticounterfeiting strategy based on electrospun security marking was developed for the induction of dual-mode security marks on cellulosic documents and banknotes.